Effect of CuO additive on the sintering and performance of niobium-doped strontium cobaltite as oxygen separation membranes - Zhao, J.; Chen, D.; Shao, Zongping; Liu, Shaomin (Elsevier Science Ltd, 2010)
In this work, the effects of CuO addition on sintering behavior, crystal structure and the oxygen permeation of SrCo0.9Nb0.1O3−δ (SCN) membranes have been investigated. XRD characterization demonstrated that copper could incorporate into the perovskite lattices with certain solubility dependent on temperature. Small amount of CuO (5 wt.%) successfully reduced the sintering temperature of the SCN membrane by 180 °C. A relative density of 95.4% was reached for the membrane with 5 wt.% CuO additive after sintering at 1000 °C. The promoting effect on sintering is likely associated with liquid assisted sintering. The incorporation of copper into the SCN lattice has minimal effect on the membrane sintering but a significant effect on the membrane integrity. As compared to the single-phase SCN membranes, the introduction of CuO as a sintering aid does not affect the electronic conductivity of the membrane between 700 and 900 °C, but the oxygen permeability is slightly reduced. Permeation study of the membranes of 0.9 mm thickness demonstrated oxygen fluxes of 1.5, 1.4, 1.3 and 1.2 ml cm−2 min−1 [STP] at 800 °C for the membranes containing 0 (pure SCN), 1, 3 and 5 wt.% CuO, respectively. The results suggest that the introduction of CuO as a sintering aid had a more significant effect on the oxygen surface exchange kinetics than on the oxygen bulk diffusion rate.